2017
DOI: 10.1111/sjop.12374
|View full text |Cite
|
Sign up to set email alerts
|

Child and family‐related predictors of psychological outcomes in children adopted from abroad; what is the role of caregiver time?

Abstract: International adoptees need to cope with stressful transitions and to develop secure attachment with their caregivers at the same time. Although most children adopted from abroad adjust fine, they are at increased risk of psychological problems. We investigated whether both child and family-related factors are associated with later psychological problems and whether the length of time spent at home after adoption before daycare moderates these associations among internationally adopted children in Finland (Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…These findings were only partially corroborated in a US study of 1948 internationally adopted children where adoption at age 2 years or later predicted both externalizing and internalizing behavior problems independent of institutional rearing [ 25 ]. A Finnish study of 1265 international adoptees found no linear effect of time of arrival to Finland [ 29 ]. A possible effect of early adversities may change with age at assessment, Sonuga-Barke et al found a catch-up on cognitive impairment, but increasing emotional problems before young adulthood [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were only partially corroborated in a US study of 1948 internationally adopted children where adoption at age 2 years or later predicted both externalizing and internalizing behavior problems independent of institutional rearing [ 25 ]. A Finnish study of 1265 international adoptees found no linear effect of time of arrival to Finland [ 29 ]. A possible effect of early adversities may change with age at assessment, Sonuga-Barke et al found a catch-up on cognitive impairment, but increasing emotional problems before young adulthood [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…El objetivo del trabajo ha sido conocer el estado actual de las dificultades de IS en niños huérfanos, institucionalizados y adoptados, ya que, en ocasiones, dichos problemas no son evidentes. En los trabajos de Purvis et al (2013), Rita et al, (2017) y Wade et al, (2019) se indica que los déficits presentados en los niños institucionalizados o adoptados se correlacionarían positivamente con problemas en el procesamiento sensorial, ya que los niños presentan déficits de coordinación, propiocepción, vestibulares, táctiles, auditivo y olfatorios, y en general presentan déficit en la función ejecutiva. La mayoría de los artículos analizados evalúan a través de diversas escalas el desarrollo y la conducta del niño, mostrando mayores dificultades los niños institucionalizados que los que no lo han estado nunca (Elovainio et al, 2015;McDermott et al, 2013).…”
Section: Discussionunclassified
“…Es importante considerar los posibles sesgos que pueden influir en los resultados de los estudios examinados, los identificados se detallan a continuación: Sesgo de Selección de la Muestra: Varios estudios se centraron en grupos de población muy específicos, como niños adoptados (Tirella et al, 2012;Rita et al, 2017), mujeres embarazadas (Branjerdporn et al, 2020(Branjerdporn et al, , 2021a y bebés prematuros (Weiss, 2005). Estos hallazgos no necesariamente se pueden generalizar a la población en su conjunto-Sesgo Metodológico: Se observó el uso de enfoques cualitativos en algunos estudios, como los estudios de caso (Hendricks & McPherson, 2010) y los análisis de diarios y correos electrónicos (Hendricks & McPherson, 2010).…”
Section: Riesgo De Sesgounclassified